Review of E. Robinson's History, Heritage and Tradition in Contemporary British Politics: Past Politics and Present Histories - Salvanou, Emilia (Historein, 2013)
Emily Robinson, History, Heritage and Tradition in Contemporary British Politics: Past Politics and Present Histories, Manchester: Manchester University Press, 2012. 208 pp